2010
DOI: 10.1016/j.jacc.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Visualization of Coronary Artery Endothelial Function in Healthy Subjects and in Patients With Coronary Artery Disease

Abstract: Endothelial-dependent coronary artery dilation and increased blood flow in healthy subjects, and their absence in CAD patients, can now be directly visualized and quantified noninvasively. Local coronary endothelial function differs between severely and mildly diseased arteries in a given CAD patient. This novel, safe method may offer new insights regarding the importance of local coronary endothelial function and improved risk stratification in patients at risk for and with known CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
196
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(221 citation statements)
references
References 45 publications
21
196
4
Order By: Relevance
“…Only recently has MRI been used to assess coronary endothelial vasomotion in subjects with coronary artery disease. [27][28][29] In the present study, we showed that endothelial damage was accompanied by an impaired endothelial-dependent vasodilation in response to acetylcholine. Both the atherosclerotic ApoE Ϫ/Ϫ mice and WT animals injected with RVV showed vasoconstriction compared with uninjected WT animals that showed vasodilation.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Only recently has MRI been used to assess coronary endothelial vasomotion in subjects with coronary artery disease. [27][28][29] In the present study, we showed that endothelial damage was accompanied by an impaired endothelial-dependent vasodilation in response to acetylcholine. Both the atherosclerotic ApoE Ϫ/Ϫ mice and WT animals injected with RVV showed vasoconstriction compared with uninjected WT animals that showed vasodilation.…”
supporting
confidence: 59%
“…[22][23][24][25][26] Recently, MRI has also been used to assess endothelial function. [27][28][29] Gadofosveset is a clinically approved gadolinium-based contrast agent that reversibly binds to serum albumin, resulting in a prolonged vascular presence and a 5-to 10-fold increase in relaxivity (r 1 ). 30,31 Gadofosveset is predominantly present within the vessel lumen but may enter the vessel wall through leaky neovessels 32,33 and mechanically damaged endothelium.…”
Section: Clinical Perspective On P 719mentioning
confidence: 99%
“…[15][16][17][18][19][20] Providing reliable techniques to identify atherosclerotic lesions in the early stages, however, is still challenging. In this study, we could show that alterations of local vascular elasticity precede the formation of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Although MRI has recently been used to quantify impaired vascular elasticity via global PWV, 24 vascular distensibility, 25 and endothelial function 18,20 in humans, those studies were limited to patients with morphologically manifest atherosclerosis. PWV and vascular distensibility are parameters describing the arterial stiffness, which is primarily determined by the extracellular matrix, whereas the endothelial function measures the ability of the endothelium to regulate vascular tone in response to a variety of stimuli such as acetylcholine or physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Technological advances in MRI, image processing software, and development of molecular imaging agents have improved the characterization and measurement of most of these parameters and provide a promising tool for the noninvasive assessment of atherosclerotic disease. MRI sequences that allow velocity mapping of the coronary arteries 46,47 are now available and could be used for the calculation of ESS in the coronary tree.…”
Section: Discussionmentioning
confidence: 99%